Rat tail models for the assessment of injectable nucleus pulposus regeneration strategies. Issue 3 (11th July 2022) - Barcellona, Marcos N.; McDonnell, Emily E.; Samuel, Shani; Buckley, Conor T.
Abstract: Back pain is a global epidemiological and socioeconomic problem often associated with intervertebral disc degeneration; a condition believed to initiate in the nucleus pulposus (NP). There is considerable interest in developing early therapeutic interventions to target the NP and halt degeneration. Rat caudal models of disc degeneration have demonstrated significant utility in the study of disease progression and its impact on tissue structure, composition, and mechanical performance. One significant advantage of the caudal model is the ease of access and high throughput nature. However, considerable variability exists across the literature in terms of experimental setup and parameters. The objective of this article is to aid researchers in the design and development of caudal puncture models by providing details and insight into the most reported experimental parameters. Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines were employed to screen the existing literature and 80 manuscripts met the inclusion criteria. Disc geometry, surgical approaches, effect of needle gauge size to induce degeneration, therapeutic volume, outcome measures, and associated limitations are considered and discussed, and a range of recommendations based on different research questions are presented. Abstract : A systematic review on the most reported experimental parameters of rat tail models. Providing a guide to researchers in the design and development of puncture models based on different research questions.